A Digital Transformation Framework for U.S. E-Commerce Supply Chains - Oluwakemi Famoti,; Bamidele Michael Omowole,; Godwin Nzeako,; Rahman Akorede Shittu,; Ogechukwu Nwanneka Ezechi,; Chikezie Paul-Mikki Ewim,; Hope Ehiaghe Omokhoa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid advancement of digital technologies has transformed industries worldwide, with U.S. e-commerce supply chains being no exception. This concept paper presents a comprehensive framework for digital transformation within U.S. e-commerce supply chains, aiming to enhance efficiency, resilience, and scalability in an increasingly competitive market. The framework outlines the integration of cutting-edge technologies, including artificial intelligence (AI), blockchain, Internet of Things (IoT), and big data analytics, to optimize key supply chain operations such as inventory management, logistics, demand forecasting, and customer service. The paper identifies the critical challenges U.S. e-commerce supply chains face, such as fragmented data systems, inefficiencies in real-time decision-making, and vulnerabilities to external disruptions. To address these challenges, the framework proposes a phased approach to digital transformation, prioritizing automation, data integration, and real-time analytics. It emphasizes the importance of adopting cloud-based solutions for enhanced scalability and collaboration between suppliers, distributors, and retailers. In addition to technological solutions, the framework highlights the role of human capital in driving successful transformation, calling for upskilling and reskilling initiatives to prepare the workforce for a data-driven and technology-enabled environment. The paper also considers the regulatory and cybersecurity aspects of digital transformation, offering strategies for ensuring compliance and protecting sensitive supply chain data from cyber threats. By implementing this digital transformation framework, U.S. e-commerce businesses can achieve higher levels of operational efficiency, reduced costs, and improved customer satisfaction. The framework serves as a roadmap for companies to navigate the evolving digital landscape, ultimately positioning U.S. e-commerce supply chains for sustained growth and competitive advantage in the global market.
Keywords: E-Commerce; Digital; Supply Chain; Transformation; Framework